Spanish News. Telephone conversation : memorandum of interview - McDonald, Florence
016a-0069-001 MEMORANDUM OF INTERVIEW. Date 9th February, 1937 Time 11.10 to Reference FEM/MT/550 Present Miss McDonald Mr. Carney. SUBJECT. "Spanish News". Telephone Conversation. The "Spanish News" telephoned and said they had an important telegram and wanted to speak to Sir Walter. I then went to the telephone and explained that Sir Walter was in a meeting but offered to take down the telegram on the telephone. They said that they could speak to no one but Sir Walter. I repeated that Sir Walter was engaged and he had asked me to take the message. Then I asked who was actually speaking on the telephone and was told that it was Mr. Carney, He was very brusque in his manner and said, "Very well, we will put that in the story then, that Sir Walter won't speak to us" and rang off. 292/946/16a/70